Analysis, manifolds and mechanics proceedings - Chaki B ed.; International Symposium on Analysis, Manifolds and Mechanics; International symposium on analysis, manifolds and mechanics Kolkata, India 5-7 Feb 2003 (Kolkata M C Chaki Centre for Mathematics and Mathematical Sciences, 2003)
The papers focus the discussions in parallel sessions covered different facets of analysis and differential geometry and their applications to relativity and cosmology, quantum mechanics also fuzzy systems.
The symposium is organised in honour of Prof. M C Chaki's 90th birth anniversary
Keywords: Analysis; Manifolds(Mathematics)